Florida 4-H Treasurer's Manual and Record Book - Judith Levings; Ali Baker; Sarah Hensley; Stacey Ellison (EDIS, 2014)
Being the treasurer is a very important position in your club. Your fellow 4-H Club Members have shown their confidence in you by letting you have this responsibility. As treasurer, you will be responsible for taking care of the club’s money, bank accounts, or other money matters. This 32-page manual and record book has been updated by Judith Levings, Ali Baker, Sarah Hensley, and Stacey Ellison, and published by the UF Department of 4-H Youth Development, September 2014.